Confronting Pension Reform: Public Employees' Psychological Contract Breach, Negative Perception, Regret, and the Moderating Role of PSM. (December 2022) - Mussagulova, Assel; Chen, Chung-An; Dennis Dong, Hsiang-Kai
Although pension reform has been a global trend in the last couple of decades, public administration research has seldom addressed the issue of how targeted pension reforms affect civil servants. The goal of this study is to conceptualize pension reform as the breach of the psychological contract between the government and civil servants and to understand whether it leads to the experience of regret in civil servants over choosing a government career. In doing so, this study also explores the possible role of public service motivation (PSM) in moderating the experience of regret elicited by psychological contract breach as well as the negative perception of the pension reform. The analysis of the data collected from 944 Taiwanese public employees shows that (i) both psychological contract breach and negative perception trigger regret and (ii) PSM strengthens the impacts of psychological contract breach and the negative perception of the pension reform. The findings have critical implications for both practitioners handling pension reforms and researchers interested in building a theory of PSM.